Reduction of bacteria in storage system of sewage effluents - Al‑Gheethi, A. A.; Mohamed, R. M.; Efaq, A. N.; I., Norli; M., R. Adib; H. M., K. Amir (Springer International Publishing, 2017)
The present work is aimed to investigate the linear regression model of total coliform (TC), faecal coli-form (FC) and enterococci (ENT) responses in the storage system of sewage effluents at different temperatures (room temperature 25 ± 2 °C, 55 and 65 °C). Five litres (v/v) of sewage effluent samples was stored at room temperature (25 ± 2 °C) for 1, 2, 3 and 4 weeks. In order to investigate the response of bacteria to the storage system at thermal conditions, the sewage samples were stored at the tempera-tures of 55 and 65 °C in a water bath shaker for 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110 and 120 min, respectively. The results indicated that the storage system at room tem-perature significantly (p < 0.01) effected the reduction of TC (33%), FC (36.6%) and ENT (47.8%). Moreover, sew-age effluent met WHO guidelines after two weeks of stor-age period at room temperature. The storage system at 55 and 65 °C had more significant influence (p < 0.01) on TC, FC and ENT. The reductions for TC, FC and ENT were 49.6 versus 64, 47.7 versus 83.2% and 47.4 versus 57.3%, respectively. ENT (Gram-positive bacteria) exhibited more resistance to the storage system at 65 °C than TC and FC (both are Gram-negative bacteria). This might be due to the differences in the cell wall structure. It can be concluded that the storage system of sewage effluents has a significant potential for the reduction of indicator bacteria.